STUDY OF HOLIDAY-RELATED LEXICAL UNITS IN UZBEK AND GERMAN LANGUAGES (Scientific journal of the Fergana State University, 2024)
This article will provide a linguistic and cultural analysis of the lexical units of the Uzbek and German languages associated with the holiday of Navruz ”and,,, Ostern” (Easter), as well as identify their similarities and differences using the example of the Uzbek and German languages.